SOSIALISASI PEMASARAN PRODUK UMKM SECARA ONLINE - Zaki Ainul Fadli; Fajria Noviana; Nur Hastuti (Departemen Linguistik, Fakultas Ilmu Budaya Universitas Diponegoro, 2021)
UMKM is one of the pillars of the national economy. UMKM has great potential to continue to grow and develop despite the market trends that are starting to shift from offline to online. Therefore, it takes effort to provide ways and strategies to sell online. This community service was held with the aim to provide an understanding of the online marketing of UMKM products. The method used in online socialization is in the form of lectures, discussions, and questions about Online UMKM Product Marketing, which is divided into two sessions with two different subthemes: the first session with the title